Tần số góc và kích thước phá hủy động đất trận động đất Điện Biên - Thành, Trần Thị Mỹ (Vietnam Journal of Earth Sciences, 2012)
SummaryCorner frequency and rupture area of Dienbien earthquakeone of the most important parameters of the earthquake source model is the affected area at the source. Generally, this area is determined byobservation instruments or by estimation from calculations based on equations related to the released energy such as magnitude. Brune (1970) considered this affected area is a function of the corner frequency. In this paper, we undertake the calculations of the earthquake damaged area at Dien Bien and a few aftershocks… by determining this corner frequency of these earthquakes